2017
DOI: 10.1109/jbhi.2016.2633509
|View full text |Cite
|
Sign up to set email alerts
|

Portable mTBI Assessment Using Temporal and Frequency Analysis of Speech

Abstract: This paper shows that extraction and analysis of various acoustic features from speech using mobile devices can allow the detection of patterns that could be indicative of neurological trauma. This may pave the way for new types of biomarkers and diagnostic tools. Toward this end, we created a mobile application designed to diagnose mild traumatic brain injuries (mTBI) such as concussions. Using this application, data were collected from youth athletes from 47 high schools and colleges in the Midwestern United… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
16
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 20 publications
(16 citation statements)
references
References 26 publications
0
16
0
Order By: Relevance
“…Rate -Previous research found changes in basic parameters of the voices of individuals following a concussion, primarily in their fundamental frequencies and variability 31,32 . However, no study to date has described a formal subjective evaluation of rate in this population.…”
Section: Perceptual Ratingsmentioning
confidence: 99%
“…Rate -Previous research found changes in basic parameters of the voices of individuals following a concussion, primarily in their fundamental frequencies and variability 31,32 . However, no study to date has described a formal subjective evaluation of rate in this population.…”
Section: Perceptual Ratingsmentioning
confidence: 99%
“…A second study by McHenry found the most frequently occurring abnormality among those with severe TBI to be amplitude perturbation, followed by voice turbulence index, with nearly a quarter of the research volunteers showing abnormalities in all of the five voice measurements [80]. While interest remains in identifying and using speech acoustic features as biomarkers for portable diagnostic tools for TBI [81], the field remains in its' infancy. Research has focused on severe TBI.…”
Section: Voice Analysismentioning
confidence: 99%
“…Contect is an early warning medical application that seeks to detect possible neurological complications (e.g., concussions, traumatic brain injuries) by analyzing a patient's speech [26,27]. Specifically, it asks the patient to take a sustained vowel test (to say "AHHH" for as long as possible), records the audio, and then feeds the speech sample to a deep learning neural network that processes the sample and delivers a concussion probability.…”
Section: Contectmentioning
confidence: 99%